Pyrrolidine dithiocarbamate attenuates the development of acute and chronic inflammation - Cuzzocrea, Salvatore (2002)
1. The nuclear factor-κB (NF-κB) is a transcription factor which plays a pivotal role in the induction of genes involved in physiological processes as well as in the response to injury and inflammation. Dithiocarbamates are antioxidants which are potent inhibitors of NF-κB. 2. We postulated that pyrrolidine dithiocarbamate (PDTC) would attenuate inflammation. In the present study we investigate the effects of PDTC in animal models of acute and chronic inflammation (carrageenan-induced pleurisy and collagen-induced arthritis). 3. We report here for the first time that PDTC (given at 100, 30 or 10 mg kg(−1) i.p. in the pleurisy model or at 10 mg kg(−1) i.p. every 48 h in the arthritis model) exerts potent anti-inflammatory effects (e.g. significant reduction of (A) pleural exudate formation, (B) polymorphonuclear cell infiltration, (C) lipid peroxidation, (D) inducible nitric oxide synthase (iNOS) activity and nitric oxide production (E) plasma and pleural exudates levels of interleukin-1β and tumour necrosis factor-α, (F) histological injury and (G) delayed development of clinical indicators). 4. Furthermore, PDTC reduced immunohistochemical evidence of (A) formation of nitrotyrosine, (B) activation of poly (ADP-ribose) polymerase (PARP), (C) expression of iNOS and (D) expression of cyclo-oxygenase-2 (COX-2) in the lungs of carrageenan-treated mice and in the joints from collagen-treated mice. 5. Additionally, Western blotting and immunohistochemical analysis of lung tissue revealed that PDTC prevented degradation of IKB-α and translocation of NF-κB from the cytoplasm into the nucleus. 6. Taken together, our results clearly demonstrate that prevention of the activation of NF-κB by PDTC reduces the development of acute and chronic inflammation. Therefore, inhibition of NF-κB may represent a novel approach for the therapy of inflammation.